التربية الصحية المدرسية للطلاب المصابين بالأمراض المزمنة - سلامي, فوزية; بوهناف, عبد الكريم (جامعة الوادي - University of Eloued, 2023)
لم يعد من النادر أن نصادف حالات متعددة ومختلفة من الطلبة المصابين بالأمراض المزمنة داخل الأوساط المدرسية وفي مختلف الأطوار التعليمية، هؤلاء الطلبة اللذين يتميزون بخصائص شخصية تتطلب من كل الأطراف القائمة على عملية التربية والتعليم من بذل جهود إضافية في مختلف المجالات التربوية لتحقيق أكبر الفرص الممكنة لهم في حق التعلم في المدارس العادية في ظروف صحية ملائمة. لذلك هدفت الدراسة إلى البحث عن كيفية تطبيق التربية الصحية للطلبة المصابين بالأمراض المزمنة داخل الأوساط المدرسية من أجل استغلال كل الميادين الممكنة لتطبيق اشتراطات الصحة بها داخل المدارس بعد التعرف على ماهية الأمراض المزمنة وسمات الطلبة المصابين بها واحتياجاتهم، وتوصلنا إلى أن ذلك يتم عبر ثلاث مجالات كبرى هي الوقاية عن طريق التغذية والرياضة المدرسية ووحدة المتابعة والصحة المدرسية، الإسعافات الأولية، التثقيف الصحي المدرسي. Abstract: It is no longer rare to encounter multiple and different cases of students with chronic diseases within the school community and in the different educational stages. Those students who are characterized by personal characteristics that require all parties involved in the educational process to make additional efforts in various educational fields to enable them to have the right to learn in regular schools. in suitable sanitary conditions. Therefore، the study aimed to search for how to implement health education for students with chronic diseases within the school community to exploit all possible areas to implement health requirements within schools after identifying chronic diseases and the characteristics of students with chronic diseases. and their needs، and we concluded that this is done through three main areas which are through prevention through nutrition and school sports، first aid ، and school health education.
مقال
Keywords: أمراض مزمنة ؛ تربية صحية ؛ وقاية ؛ إسعاف أولي ؛ تثقيف صحي; chronic disease ; healthy education; First aid ; Health education